The Strategic Role of Zakat Management in Socio-Economic Empowerment of the Ummah - Sabil Mokodenseho; Prayascita Paputungan; Aisa Paputungan; Nazria Modeong; Tetriana Manggo; Serli Kobandaha; Sarini Dilapanga; Yuniarti Imban (West Science Islamic Studies, 2024)
Zakat, one of the five pillars of Islam, holds significant potential for socio-economic empowerment within Muslim communities. This research delves into the strategic role of zakat management in Indonesia's socio-economic empowerment of the Ummah through a qualitative lens. Employing qualitative analysis, this study explores the mechanisms, challenges, and successes of zakat management in Indonesia and its impact on the socio-economic well-being of the Ummah. Through in-depth interviews, document analysis, and thematic coding, the research uncovers critical insights into how zakat management can be strategically leveraged to uplift the Ummah in Indonesia. The findings shed light on the importance of effective zakat management frameworks, institutional collaborations, and community engagement in fostering socio-economic empowerment among the Ummah.